ANTIPROLIFERATIVE ACTIVITY OF FLAVONOIDS ISOLATED FROM ECHINOPS GRACILIS O. HOFFM - CASTRO F. L. WÉYÉPÉ; WILLIAM F. FEUDJOU; CAROLE A. AMBONO; HERMIA N. IKOME; MARIUS M. BALEMAKEN; PIERRE J. ABDOU; THÉODORA K. KOPA; GABRIEL A. AGBOR; ALEMBERT T. TCHINDA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Apigenin-7-O-(4′′-feruloyl)-β-D-glucopyranoside (1) were isolated from the methanol extract of aerial part of Echinops gracilis, together with apigenin-7-O-(4′′-trans-p-hydroxycinnamoyl)-β-D-glucopyranoside (2) and apigenin-7-O-β-D-glucopyranoside (3). Compound (1) previously displayed antioxidant and antibacterial activity. The present study aims at evaluating the antiproliferative potential of flavonoids, isolated from the aerial part of E. gracilis O. Hoffm. The effect of compounds (1), (2) and (3) on the viability of HeLa cells was determined by the method of 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay at different concentrations. The ability of compounds to induce the cell death was evaluated by using acridine orange/ethidium bromide (AO/EtBr) staining. Compound (1) induced an effective change in the cell viability of HeLa cells with IC50 concentration value of 27.36 µgmL-1. Induction of cell death alteration in cell morphology and cancer cell population was observed in cells treated with compound (1), which makes it behave as a potent synergistic antiproliferative agent against HeLa cells.